Benchmarking, as an innovative mechanism for the development of tourist industry of Kazakhstan (Journal of Economic Research & Business Administration, 2017)
Benchmarking in the tourism sector - an ongoing process of study andevaluation of tourism products and experience their most serious competitorsor those travel agencies that are recognized by business leaders (notnecessarily direct competitors, and not necessarily just the tourism industryof the company). This search for the best experience of commercial activity,which leads to an advantage in the tourism business. It involves theprocess of assessing the internal state of things in the travel agency andthe external evaluation, which is based on certain objective facts that arecontinuously collected.The article describes the international experience and the importanceof using awards in the tourism industry to improve the company’s competitiveness.Also investigated the company leaders in the tourist marketof Kazakhstan in different areas, which experience can use the other participantsof this market.